Biomechanical Joint Demands and Functional Outcomes During Manual Wheelchair Use in Pediatric Patients with Spinal Cord Injury - (:unkn) unknown (My University, 2014)
The biomechanical demands of the upper extremities (UEs) during pediatric manual wheelchair (MWC) use have not been fully explored. Children who use MWCs for mobility engage in a range of functional activities that may place large biomechanical demands on the UEs leading to a high risk on overuse injuries. This study aims to analyze the kinematics and kinetics of pediatric manual wheelchair use during propulsion, starting, stopping and weight relief tasks. Fourteen pediatric patients with spinal cord injury were recruited and data were collected using a 14-camera Vicon MX motion analysis system (Oxford Metric Group, Oxford, UK) and a SmartWheel system (Out-Front, Mesa, AZ). Additionally, pain and health-related quality of life outcomes were analyzed to identify correlations with kinematic and kinetic data. The weight relief task was found to be the most demanding, resulting in superior forces on the glenohumeral (GH) joint that were more than nine times greater during weight relief, 21.19 % body weight (BW) than during propulsion, 2.43 %BW. Stop task GH joint forces were higher in the inferior direction (9.68 %BW) and lower in the posterior direction (0.14 %BW) when compared to propulsion (6.85 %BW and 1.99 %BW respectively). Start task biomechanics were the least demanding with minimal statistical differences found from the demands of propulsion. Outcomes of pain were reported on the visual analog scale (VAS) with only one subject reporting an average daily pain of 15 on a scale of 0 to 100. Mean physical health scores (PCS) and mental health scores (MCS) from the Short-Form 12 Health Questionnaire (SF-12) were 44.3 and 56.3 respectively, indicating lower than normal physical health and higher than normal mental health in this population (norm=50). Clinical intervention is recommended to decrease the biomechanical demands of functional mobility through appropriate training methods to reduce the risk of UE overuse injuries.
Keywords: Biomechanics; Pediatric; Spinal Cord Injury; Upper Extremity; Wheelchair